Quorum sensing attenuation properties of ethnobotanically valuable lichens against Pseudomonas aeruginosa - ÇOBANOĞLU, GÜLŞAH; SESAL, NÜZHET CENK (TAYLOR & FRANCIS LTD, 2020)
Antimicrobial properties of ethnobotanically valuable lichens are well recognized but it is not known how exactly their therapeutic effects on microbial infections occur. Pseudomonas aeruginosa is an opportunistic Gram-negative pathogen and its nosocomial strains are responsible for high mortality and morbidity rates. It coordinates pathogenesis and virulence via four quorum sensing (QS) mechanisms called las, rhl, pqs and iqs. The objective of this study is to investigate and report the utilization of lichens for QS inhibition against P. aeruginosa. The inhibitory potentials of Ramalina farinacea (L.) Ach. and Platismatia glauca (L.) W.L. Culb. & C.F. Culb extracts were tested against QS systems of P. aeruginosa using biosensor strains (lasB-gfp, rhlA-gfp and pqsA-gfp). All tested lichen acetone extracts have shown inhibitory effects on las, rhl and pqs QS systems. The percentages of QS inhibition were detected between 75.21% and 92.42% for las, 50.62% and 64.22% for rhl, 47.61% and 69.35% for pqs systems. The highest inhibition was detected for the extracts of R. farinacea collected from Bursa-Alacam. We concluded that these lichen species have significant anti-QS potentials against P. aeruginosa and they can be further evaluated as alternative biosources in medicine.
Keywords: Ramalina farinacea; Platismatia glauca; lichen extracts; Pseudomonas aeruginosa; quorum sensing inhibition; ANTIMICROBIAL ACTIVITY; SECONDARY METABOLITES; RAMALINA-FARINACEA; PLATISMATIA-GLAUCA; BIOFILM BACTERIA; USNIC ACID; ANTIOXIDANT; INHIBITORS; EXTRACT; NETWORK